Adsorption Of Methylene Blue Using Active Charcoal From Empty Fruit Bunch (EFB) - Teguh Wirawan; Ishak Wiradikara Az; Noor Hindryawati (JURNAL KIMIA MULAWARMAN, 2023)
Research on the adsorption of methylene blue by activated charcoal from Empty Fruit Bunch (EFB) has been carried out. This study aimed to synthesize activated charcoal from EFB, characterize it, and use it as an adsorbent for methylene blue. Activated charcoal was synthesized by carbonation in a furnace at 300oC for 1 hour. Chemically, activation was carried out by immersion in HCl solution for 24 hours. Characterization was carried out by proximate test, determination of functional groups using Fourier Transform Infrared (FT-IR), and determining material shape with X-Ray Diffraction (XRD). The study of activated charcoal adsorption as methylene blue adsorbent was carried out by treating variations in contact time, adsorbent weight, and concentration. The results of the proximate test with the parameters of surface area, moisture content, and ash content were 162.12 m2/g, 0.52%, and 5.27%, respectively. The results of the FT-IR characterization test showed an aromatic C–H, C=C and C–O. Based on the results of characterization with XRD giving a pattern at a diffraction angle of 2 20 - 30o, it was seen that there was a wide peak, which indicated that it had an amorphous structure. The optimum conditions for methylene blue adsorption occurred at a contact time of 40 minutes, and the adsorbent weight was 0.1 g for 10 mL of 50 ppm methylene blue. The adsorption of methylene blue followed the Freundlich isotherm adsorption pattern and had a maximum adsorption capacity of 8.92 mg/g.